The practice of procedural pain assessment and management in neonatal intensive care unit in Ethiopia: Cross‐sectional study - Emebet Assefa; Mamude Dinkiye; Temesgen Geleta; Temesgen Tantu; Mekete Wondwosen; Dereje Zewdu (Health Science Reports, 2022)
Abstract Background and Aims Neonates in intensive care units undergo frequent painful procedures for diagnostic or care‐related purposes. Untreated pain has serious short‐term and long‐term complications. This study aims to evaluate the frequency of painful procedures, pain assessment, and their analgesic management practice among neonates admitted to the NICU. Methods The present study is a hospital‐based cross‐sectional study of neonates admitted at level II NICU of St. Paul hospital millennium medical college in Ethiopia between March and August 2019. Data were collected from medical charts of neonates and bedside observation using a checklist. The parameters included were demographic characteristics, types of painful procedures, pain assessment practice, and analgesic intervention provided during painful procedures. Descriptive statistics, Mann‐Whitney U‐test, and Kruskal‐Wallis test were used to compare the number of painful procedures and influencing factors. P‐value < .05 was considered statistically significant. Results Of the 325 neonates included in this study, a median of 4 (3‐7) painful procedures were performed per neonate in the first 24 hours of NICU stay. Heel lance 280 (20.7%) and Venipuncture 249 (18.41%) were the most commonly performed painful procedures. Of the 1352 painful procedures, none of the neonates received any form of analgesic intervention and none of the neonate's pain scores were documented on their medical chart. The higher number of painful procedures were associated with gestational age between 28 and 31 weeks, birth weight less than 1500 g, and use of CPAP respiratory support P‐value <.001, <.001, and .0015, respectively. Conclusion Painful procedures were frequently performed in NICU without any form of analgesic intervention. Strategies to introduce neonatal pain assessment and their analgesic management for clinical practice are necessary.